THE DEVELOPMENT OF BIOTECHNOLOGY’S LEARNING INSTRUMENTS ORIENTED HIGHER-ORDER THINKING AND THE UTILIZATION OF NATURAL RESOURCES TUNDA'S ISLAND POTENTIAL - Fitri, Siti Gia Syauqiah; Hendriyani, Mila Ermila; Sari, Indah Juwita (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2017)
Abstract Science and technology learning should not just provide a collection of facts, laws and theories but rather is a process conducted by the students to acquire knowledge through interaction with the surrounding environment. The students are trained in scientific thinking critically, creatively and independently through active and meaningful learning process, for example by using the environment as a learning resource. This study aims to develop learning equipments oriented higher-order thinking skills (critical and creative) to explore the potential of biological resources of Tunda island, as a learning resource in the subject of Biotechnology. This study used research and development (R & D) method, which consists of the stages of analysis, design, validation and revision. Learning equipments that produced are RPS (lesson plans for 1 semester), the student worksheets (LKM), and evaluation (test) instruments. The results of the validation team of experts showed that the learning equipments are good categorized, with the values 77.14 for RPS, 85 for LKM, and 94 for instrument test. Criticisms and suggestions from the experts were used as the basis of revision, so that the learning equipments are eligible for learning. Keywords: Research and Development, Tunda Island, Critical Thinking, Creative Thinking, Biotechnology Subject